School Culture-Based Character Education Implementation Patterns at Madrasah in Medan and Banda Aceh - Wati Oviana; Eva Nauli Taib; Misbahul Jannah; Rafidhah Hanum (AL-ISHLAH: Jurnal Pendidikan, 2023)
Character education is one of the goals of National education. The implementation of character education is a must in national policy through the curriculum. This study aims to describe the implementation of character education in Madrasas in Aceh and Medan. The data obtained is based on information obtained from the head of the madrasa, the deputy head of the madrasa and teachers. The sampling technique uses a purposive sampling technique. The madrasas chosen were madrahs in the city of Medan and Aceh, which the community chose.The research method uses descriptive methods with data collection techniques through interviews and document analysis. The results of the study show that the implementation of character education in Madrasahs in Medan and Aceh is realized through the formulation of a vision and mission, the preparation of curriculum and non-curriculum programs with character nuances and the provision of facilities and conditioning of the school environment with character nuances.